Relative Quantification Method as A Tool for Viral Load Assessment In COVID-19 Patients at A Tertiary Care Hospital - Mohan, Sneha; Dey, Sneha; Singh, Kushal; Chaudhary, Azra Ferheen; Kakru, Dalip; Manjhi , Mukesh; Bharti, Abhishek (Journal of Neonatal Surgery, 2025)
Background: Since March 2020 till date, there has been a continuous increase in the epidemic curve in our country. The 2‐ΔΔCt method is commonly used for viral load assessment in relative quantification methodology. The viral load detection has important implications in assessing the transmission risk associated with high viral load in any patient and protecting the disease's progression and thus holds an important role in early antiviral treatment for all critically ill patients with COVID-19. The aim of the study is to use the relative quantification method (2-∆∆Ct method) to calculate the viral load in non hospitalized population. Methods: 285 were confirmed positive for SARS‐CoV‐2 infection using Bio-Rad real-time RT-PCR test. Relative quantification was calculated by the difference of the comparative threshold cycle (ΔΔCt) between RdRp gene and RNase P genes, from the clinical sample and the positive control tested simultaneously. The association between Ct values and various factors related to disease was calculated using appropriate statistical tests. Results: The age ranging from 10-19 years showed the highest mean viral load (2∆∆ Ct value= 80.41), which was not detectable after day 9. The mean viral load 2^-∆∆Ct in SARS-CoV-2 infected patients without any comorbidities was 30.79, while patients with comorbidities showed a moderate viral load 22.52. Fever and myalgia was the most common clinical presentation and were associated with mean viral load of 29.41. Conclusion: Viral load information is required to help us understand the trends in various populations. In addition, reporting the viral load using the reference material and quantifying it using the quantification method will be more useful rather than using only Ct value for viral load analysis